Expander processing conditions affect nutrient digestibility in finishing pigs fed corn-, sorghum-, wheat-, and wheat midds-based diets - Traylor, S.L.; Hines, Robert H.; Lee, D.J.; Johnston, S.L.; Sorrell, P.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Expander processing of corn-, sorghum-, wheat-, and wheat midds-based diets improved nutrient digestibility in growing pigs and, thus, the apparent digestible energy concentration in the diets. This new feed manufacturing technology was especially beneficial to the feedstuff with the highest fiber content (i.e., wheat midds).
Keywords: Swine; Expander; Corn; Sorghum; Wheat midds